O ensino de Língua Portuguesa para alunos com Transtorno do Espectro Autista e as didáticas e metodologias possíveis - Almeida, Luciano de (2023)
This work is located in the line of research Reading, Writing and Teaching, of the Postgraduate Studies in Portuguese at the Pontifical Catholic University of São Paulo (PUC-SP) and has as its theme the language teaching processes Portuguese for people with Autistic Spectrum Disorder (ASD) and didactics and possible methodologies used in inclusive and specialized schools having as a central focus the teaching of language and language for students from 03 to 10 years old of age, in their educational and social formation it is necessary to follow up base to develop cognitive and motor skills. We start from the hypothesis of how the didactics and methodologies are being applied by the professionals of the education in a context of the educational group when it comes to education inclusive must work in an evolutionary set focusing on the development and growth of the student with ASD. The problematization is proposed by the questions: What are the possible didactics and methodologies used for teaching of Portuguese language for people with autism spectrum disorder? As we can identify and evaluate the applicability of teaching materials that serve to all, a natural integration for people with spectrum disorders autistic? It was established as a general objective: to verify the didactics and methodologies possibilities used by teachers in the classroom; and as specific objectives: analyze the materials adapted by teachers their settings; and identify a way to standardize these contents. In order to answer the question of the research problem and meet the established objectives, the selected corpus formed with the results obtained, from the verification of what are the didactics and methodologies used for teaching Portuguese to people with Autistic Spectrum Disorder (ASD); and how can we identify and evaluate the applicability of teaching materials suitable for people with autism spectrum disorder (ASD)